2021
DOI: 10.1371/journal.pcbi.1008757
|View full text |Cite
|
Sign up to set email alerts
|

Using neural networks to mine text and predict metabolic traits for thousands of microbes

Abstract: Microbes can metabolize more chemical compounds than any other group of organisms. As a result, their metabolism is of interest to investigators across biology. Despite the interest, information on metabolism of specific microbes is hard to access. Information is buried in text of books and journals, and investigators have no easy way to extract it out. Here we investigate if neural networks can extract out this information and predict metabolic traits. For proof of concept, we predicted two traits: whether mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In total, we found that n = 2357 of the 8350 organisms were capable of fermentation or 28% of the total (data file S1). In earlier work with a smaller dataset (19), we found a comparable value (33%).…”
Section: Fermentative Prokaryotes Are Diversesupporting
confidence: 78%
See 3 more Smart Citations
“…In total, we found that n = 2357 of the 8350 organisms were capable of fermentation or 28% of the total (data file S1). In earlier work with a smaller dataset (19), we found a comparable value (33%).…”
Section: Fermentative Prokaryotes Are Diversesupporting
confidence: 78%
“…Reviews of fermentation have been based on information from model organisms (10)(11)(12)(13)(14)(15), which may not capture the full diversity of this metabolism. Some work, including our own, had started to accumulate information on more prokaryotes (18,19,21,22), but a full picture has still been lacking. By using a dataset of n = 8350 organisms (28% of which are fermentative), the current study paints a fuller picture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomes were searched for proteins using locus tags for genes above. Phylogenetic trees were constructed according to Hackmann and Zhang 80 . We identified habitats of organisms forming propionate, succinate, and acetate using Bergey’s Manual 81 , BacDive 82 , and information from public culture collections.…”
Section: Methodsmentioning
confidence: 99%